2015
DOI: 10.1016/j.schres.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous oxytocin levels are associated with the perception of emotion in dynamic body expressions in schizophrenia

Abstract: Lower endogenous oxytocin levels have been associated with impaired social cognition in schizophrenia, particularly facial affect identification. Little is known about the relationship between oxytocin and other forms of emotion perception. In the current study, 41 individuals with schizophrenia (SZ) and 22 demographically matched healthy controls (CN) completed a forced-choice affective body expression classification task. Stimuli included dynamic videos of male and female actors portraying 4 discrete emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 26 publications
11
51
0
1
Order By: Relevance
“…The results revealed that patients were less accurate at identifying emotions than controls and that they had significantly higher plasma oxytocin, which was positively correlated with task performance in both patients and controls. Importantly for our discussion there was a significant group-by-sex interaction, such that control women were more accurate than control men, whereas schizophrenia women were less accurate than schizophrenia men [191]. We have obtained comparable brain activation results in the fMRI studies of emotional memory discussed in the subsequent section.…”
Section: Diminished or Reversed Sexual Dimorphismsupporting
confidence: 52%
See 2 more Smart Citations
“…The results revealed that patients were less accurate at identifying emotions than controls and that they had significantly higher plasma oxytocin, which was positively correlated with task performance in both patients and controls. Importantly for our discussion there was a significant group-by-sex interaction, such that control women were more accurate than control men, whereas schizophrenia women were less accurate than schizophrenia men [191]. We have obtained comparable brain activation results in the fMRI studies of emotional memory discussed in the subsequent section.…”
Section: Diminished or Reversed Sexual Dimorphismsupporting
confidence: 52%
“…Second, consistently with the neuroanatomical sex differences, the cognitive behavioral studies reveal that in chronic schizophrenia, men present with more Page 41 of 59 A c c e p t e d M a n u s c r i p t 41 cognitive deficits than women [159][160]. Furthermore, while studies of cognitive processes mediated by the lateral frontal cortex and fronto-parietal network, tend to show typical sexual dimorphism [174,195], the studies of processes mediated by the corticolimbic system, more frequently show reversal of normal sexual dimorphisms [176][177]191]. Finally, the cognitive neuroimaging studies support a disturbance of normal sexual dimorphism in schizophrenia, but they are scarce and difficult to interpret [175,196,241].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic alteration of genes regulating OT receptor ( OXTR ) expression may be one factor influencing social cognition deficits in psychotic disorders. This effect may be greater in schizophrenia than in other psychotic disorders because of their more severe social cognition deficits (2), and in females because of the more prominent role of the OT system in women in regulating social cognition (7-9). …”
mentioning
confidence: 99%
“…OT peptide levels are altered in psychotic disorders (9-14) and are related to social cognition deficits with more pronounced associations in female patients (7-9). Adjunctive exogenous OT administration can improve social cognition in schizophrenia (15-19).…”
mentioning
confidence: 99%